Sanskrit treatises and the construction of candi at the Kampung Baru Archaeological Site, Kedah, Malaysia - Muhammad Nu’man Mohd Nasir,; Zuliskandar Ramli,; Mohd Shamsul Bahari Abd Hadi, (Penerbit UKM, 2024)
The construction of religious structures, such as the candi at the Kampung Baru Archaeological Site, was guided by ancient Sanskrit treatises such as the Manasara and Mayamata. The discovery of an ancient structure at the excavation site of Kampung Baru Kota Kuala Muda, Kedah, has opened up new opportunities for research into the monuments of Ancient Kedah. The brick structure, known as Candi Kampung Baru, bears traces of wall carvings that are remarkably well-preserved. The present study analyses whether the Candi Kampung Baru was built in accordance with these treatises. This study employed archaeological excavations, literature reviews, visual analyses, and digital reconstruction techniques. The findings indicate that the ancient Sanskrit treatises had some influence on the construction of the candi, particularly in the selection of the site and soil. However, in other aspects, local elements were incorporated, resulting in a fusion of foreign and local elements, as the builders had their own interpretation of the treatises. The presence of local elements in this temple serves as evidence that the community in Ancient Kedah did not wholly embrace foreign influences, particularly those from India.